(untitled) (Journal of Biomedical Investigation, 2025)
Background: Early diagnosis, prompt and effective treatments are the basis for the management of malaria and key to reducing the associated morbidity and mortality. Laboratory diagnostic challenges exist because clinical diagnosis is imprecise and leads to excessive use of antimalarial drugs. Thus there is need to introduce other non-invasive rapid diagnostic tools in order to achieve the goal of universal access to malaria diagnosis. Aim: The aim of this study was to determine the reliability and usefulness of urine malaria test in the diagnosis of malaria among febrile children aged 1-10 years. Materials and Methods: A cross-sectional descriptive study in which 212 febrile children aged 1-10 years were consecutively recruited. Socio-demographic and clinical data of the subjects were obtained using interviewer-administered questionnaires. Each of the subjects were screened for malaria using blood and urine based malaria test kits respectively. Blood samples from each subjects were also sent to the laboratory for malaria microscopy. Results: Out of 212 subjects studied, 38 subjects (17.9%) had malaria parasitaemia based on microscopy. The prevalence of malaria based on blood-based malaria rapid diagnostic test and urine malaria test were 21.7% and 9% respectively. Microscopy as the gold standard for malaria diagnosis compared to other diagnostic modalities. Conclusion: In view of the low sensitivity of urine malaria test in this study, there is need for further improvement in the sensitivity of urine malaria test before it can be used alone as screening/diagnostic test for malaria in our locality.